Kombinasi Tepung Tapioka Dengan Pati Sagu Terhadap Mutu Bakso Jantung Pisang dan Ikan Patin - Ariani, Dyah Ayu; Hamzah, Faizah; Efendi, Raswen (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this research was to get the best combination flour formula in makingÂ bananaâs heart and fish meatball, Â while in terms of the benefits of this research are expected to improve the utilization of sago palm as a source of local food. The method used in the research was Complete Randomized Design (CRD) with four replications of five treatments and treatment consists of TS1 (cassava flour 100 : sago starch 0), TS2 (cassava flour 75 : sago starch 25), TS3 (cassava flour 50 : sago starch 50), TS4 (cassava flour 25 : sago starch 75), TS5 (cassava flour 0 : sago starch 100).The result of the research shows that the combination cassava flour with sago starch significantly effect to the moisture content, ash content,Â Â starch content,Â taste, textureÂ and non significantly effect to the aroma, color, and overall. Based on the evaluation of organolepticÂ hedonic test of color, aroma, taste, texture and overall, the panelist gives the evaluation from like to between quite like and quite dislike to the bananaâs heart and fish sausage meatball. The best treatmentÂ from the research was TS3. Keywords: Cassava Flour, Sago Starch, Meat Ball